Cost-efficient food loss and waste management using the FANP analysis - Apiwat Krommuang; Opal Suwunnamek; Wonlop Writthym Buachoom (Frontiers in Sustainability, 2026)
This study proposes a structured cost-efficiency framework for managing food loss and waste in the frozen food industry by integrating supply chain analysis with responsibility-based cost concepts. Data collected from key industry stakeholders were used to identify critical factors contributing to food loss and waste across the frozen food supply chain. The fuzzy analytic network process (FANP) incorporated with cost analysis was employed to prioritize these interdependent factors. The results from the FANP show that suppliers and farms, followed by handling and storage. The cost responsibility analysis reveal that 85.47% of total food loss and waste-related costs are controllable, while the weighted cost impact analysis, captures the interaction between factor importance and cost proportion, indicates that factors with the highest weighted cost impacts are predominantly concentrated at the supplier and farm stage. The findings provide clear managerial guidance by identifying priority intervention areas where cost reductions can be achieved most effectively. This study contributes to the literature by linking food loss and waste drivers with controllable cost structures and by demonstrating how FANP can be applied to support cost-efficient and targeted improvement strategies in frozen food supply chains, particularly in emerging food-exporting economies such as Thailand.
Keywords: Food Waste Reduction and Sustainability; Municipal Solid Waste Management; Sustainable Supply Chain Management